Welfare recipiency, job separation outcomes, and postseparation earnings: insight from linked personnel and state administrative data - Jill Marie Gunderson; Julie L. Hotchkiss (Federal Reserve Bank of Atlanta, 2006)
This paper uses a unique personnel data set and state administrative data to follow welfare and nonwelfare hires who separate from similar jobs with the same firm. Welfare hires are more likely to separate from their job and are more likely to be on welfare after separation compared with similarly low-skilled nonwelfare hires. Those not returning to welfare, however, are no more or less likely to have moved on to a lower- or higher-paying job than nonwelfare hires.
Keywords: 330; Sozialleistungsempfänger; Aktivierende Arbeitsmarktpolitik; Schätzung; Georgia (Staat)